Mediating role of entrepreneurial orientation in the entrepreneurial munificence and business sustainability relationships of Small and Micro Enterprise Technology Based Business (SMTBRB) - Amin Mohamad M.; Chin O. (Serials Publications, 2023)
This preliminary study aims to examine the entrepreneurial orientation (EO) of the Small and Micro enterprise Technology based Rural Business (SMTBRB) entrepreneurs in Malaysia by taking Entrepreneurial Munificence (EM) as the antecedent. EM is used to explain the influence of EO as a mediator and its consequences towards SMTBRB sustainability. The survey method was employed in this study and the data was analysed using Structural Equation Modelling (SEM) multivariate data analysis. Based on the SEM analysis, it can be concluded that in SMTBRB in Malaysia, the relationship between EM and business sustainability was not mediated by EO. However, EO and EM were significant as predictors towards business sustainability. This preliminary study provides better understanding of the SMTBRB entrepreneurs for related government agencies, especially related to the support programmes for the SMTBRB entrepreneurs. Serials Publications Pvt. Ltd.